(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this paper we study the oscillation and asymptotic behavior of the third order neutral dierential equation with " of the form where is the quotient of odd positive integers. Some examples are given to illustrate the main results.